2023
DOI: 10.3390/su151310036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Enterprise Digital Transformation on Green Technology Innovation: A Quantitative Study on Chinese Listed Companies

Abstract: Promoting enterprise digital transformation is of great significance in accelerating the innovation capability of green technology and boosting green and low-carbon economic development. Therefore, based on the textual analysis of enterprise annual reports, the measurement index of enterprise digital transformation was constructed, and combined with the data of listed, A-share companies in Shanghai and Shenzhen from 2011 to 2021, a quantitative study was conducted on the relationship between enterprise digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Under the trend of digitalization, promoting the DTE provides opportunities for improving the ERGI. Many studies have noted the positive impact of DTE on green innovation [9,[63][64][65], but most studies only focus on the micro level. DTE not only affects the green innovation development of the enterprise, but also affects other innovation subjects in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Under the trend of digitalization, promoting the DTE provides opportunities for improving the ERGI. Many studies have noted the positive impact of DTE on green innovation [9,[63][64][65], but most studies only focus on the micro level. DTE not only affects the green innovation development of the enterprise, but also affects other innovation subjects in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Digital transformation is consistent with green development and provides the internal driving force for corporate green technology innovation [40]. In addition, some scholars found by constructing enterprise digital transformation measurement indicators that there is a significant positive correlation between the digital transformation of Chineselisted companies and green technology innovation, and the CEO's IT background and tax incentives play a positive regulatory role [41]. Furthermore, some scholars point out that digital transformation can increase green innovation, especially in the context of insufficient internal controls and limited institutional ownership [42].…”
Section: Digital Transformationmentioning
confidence: 99%
“…Promoting the coordinated and efficient development of enterprise green technology innovation is of great significance to the realization of high-quality economic development in China [21]. In addition, green technology innovation is an important driving force for the sustainable growth of the global economy [22][23][24]. The current research on the influencing factors of enterprise green technology innovation mainly focuses on the following three aspects: In terms of environmental regulation, relevant studies have found that it is difficult to completely rely on the means of a spontaneous market system to promote enterprise green technology innovation [25].…”
Section: Introductionmentioning
confidence: 99%